Looking South over the World's Fair Grounds (Curt Teich & Co., Inc.)
A view looking south over the World's Fair Grounds showing the General Exhibits Group in the foreground also showing Time and Fortune Pavilion, Firestone Exhibit, Paris, Thermometer, etc.